Analysis of Improving Business Performance in the Creative Industry Through Management of Human Capital, Social Capital, and Innovation Capability in the Era of Society 5.0 - Halim, Fitria; Kusuma, Rr. Chusnu Syarifa Diah; Sherly, Sherly; Panggabean, Esther Praja Anggriany; Sudirman, Acai (FIRM Journal of Management Studies, 2023)
In the era of Society 5.0, creative industry businesses must be able to optimize human capital, social capital, and innovation capability to improve business performance so that it is more optimal. This study aims to analyze the increase in creative industry business performance through managing human capital, social capital, and innovation capability in society 5.0. This study used a library and field research design with a causal associative approach. This study used a total sample of 150 samples. Data analysis confirms that human capital, social capital, and innovation capability significantly affect business performance. The implications of this research highlight the importance of organizations in the creative industries having to invest more in developing their human resources. This can be done through appropriate training, further education, skills development, and hiring. Focus on developing human resources will help improve the quality of the workforce and produce better innovation. Organizations must build and strengthen social relationships with business partners, customers, educational institutions, and related communities. Collaboration and knowledge exchange with relevant parties can help improve access to resources, market opportunities, and new ideas. Further, organizations must prioritize innovation efforts and create an environment encouraging creativity and experimentation. It is essential to develop a culture of innovation throughout the organization, encourage employees to share ideas, provide adequate support and resources, and adopt a flexible and adaptive management approach.